CREATIVE ASPECTS OF USAGE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN DESIGNER EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
The basic approaches to the use of information technologies in educational process of visual art and design are analysed in the article. Methodological aspects of ICT integration and the artistic and educational activity as well as difficulties regarding the development of teaching materials for professional thinking formation and development of the creative person are considered.
Keywords: educational process; informational technologies; integration ICT